2022
DOI: 10.1128/jvi.00408-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues Required for Inhibition of Host Gene Expression by Influenza Virus A/Viet Nam/1203/2004 H5N1 PA-X

Abstract: PA-X is a non-structural protein of influenza A virus (IAV), which is encoded by the polymerase acidic (PA) N-terminal region that contains a C-terminal +1 frameshifted sequence. IAV PA-X protein modulates virus-induced host innate immune responses and viral pathogenicity via suppression of host gene expression or cellular shutoff, through cellular mRNA cleavage. Highly pathogenic avian influenza viruses (HPAIV) of the H5N1 subtype naturally infect different avian species, they have an enormous economic impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…Our results indicate that all the amino acid changes contributed to decrease 1918 PA-X's ability to induce cellular shutoff (Figures 5 and 6). Similarly, in a previous work using an H5N1 IAV strain, we also found that amino acid mutations H146Y, and L187P, present in the double mutants, as well as F76L, found in a single mutant, decrease the ability of H5N1 PA-X to inhibit host gene expression [36].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results indicate that all the amino acid changes contributed to decrease 1918 PA-X's ability to induce cellular shutoff (Figures 5 and 6). Similarly, in a previous work using an H5N1 IAV strain, we also found that amino acid mutations H146Y, and L187P, present in the double mutants, as well as F76L, found in a single mutant, decrease the ability of H5N1 PA-X to inhibit host gene expression [36].…”
Section: Discussionsupporting
confidence: 86%
“…Empty and 1918 WT PA-X-expressing pCAGGS plasmids were included as controls. Unsurprisingly, 1918 WT PA-X was not detected in transfected cells by immunofluorescence because its ability to inhibit host gene expression, including its own expression ( Figure 4 ) [12,25,27,3236]. However, 1918 PA-X containing F76L, L109R, T123A, R168G, T98I/P103S and H146Y/L187P mutations were detectable under immunofluorescence because these 1918 PA-X mutants were affected in its shutoff capabilities ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that all the amino acid changes contributed to a decrease in 1918 PA-X's ability to induce cellular shutoff (Figures 5 and 6). Similarly, in a previous work using an H5N1 IAV strain, we also found that amino acid mutations, H146Y and L187P, present in the double mutants, as well as F76L, found in a single mutant, decrease the ability of H5N1 PA-X to inhibit host gene expression [40].…”
Section: Discussionsupporting
confidence: 86%
“…To evaluate the effect of WT and mutant PB2 and PB1 proteins on viral polymerase activity, a MG assay was performed as previously described ( 42 , 53 ). Briefly, human 293T cells (5 × 10 5 cells/well, 12-well plate format, triplicates) were transiently co-transfected in suspension, using Lipofectamine 2000 (Invitrogen), with 125 ng of each ambisense pDZ plasmids (pDZ-PB2 or PB2 LAIV , -PB1 or PB1 LAIV or -PB1 L319Q or pDZ-PB1 LAIV+L319Q , -PA, - and NP), together with 250 ng of two reporter viral (v)RNA-like expression pPOL-I plasmids encoding GFP or Gluc driven by a human RNA polymerase I promoter ( 53 , 71 ). A Cluc-encoding plasmid under the simian virus 40 promoter (SV40-Cluc, 50 ng) was included to normalize transfection efficiencies ( 72 , 73 ).…”
Section: Methodsmentioning
confidence: 99%